Dramatically enhanced electromagnetic wave absorption of hierarchical CNT/Co/C fiber derived from cotton and metal-organic-framework. (May 2020) - Yang, Minglong; Yuan, Ye; Li, Ying; Sun, Xianxian; Wang, Shasha; Liang, Lei; Ning, Yuanhao; Li, Jianjun; Yin, Weilong; Che, Renchao; Li, Yibin
Abstract: Lightweight, low-cost electromagnetic (EM) wave absorption materials are in urgent need, as EM interference pollution is increasingly serious. Carbon material as EM absorber has attracted ever increasing attention. However, their absorption property is still limited. Herein, we propose a very simple strategy to prepare hierarchical carbon fiber coated with Co/C nano-dodecahedron particles where CNTs were anchored (HCF@CZ-CNTs), using cotton and metal-organic-framework (MOF) as raw materials. One of MOF, ZIF-67 particles were in-situ grown onto the surface of cotton fibers. Lightweight HCF@CZ-CNTs samples were obtained by direct carbonization, the apparent density of which is only 0.0198 g/cm 3 . The minimum reflection loss (RLmin ) of hierarchical HCF@CZ-CNTs was dramatically enhanced to −53.5 dB at 7.8 GHz, compared with pure carbonized cotton fiber (RLmin  = −18.9 dB at 16 GHz). Meanwhile the effectively absorption bandwidth was also remarkably enlarged to 8.02 GHz. The excellent EM wave absorption performance is attributed to the micro-to-nano hierarchical hollow fibrous structure, as well as the synergetic effect of polarization relaxation and magnetic loss. These results illuminate a low-cost and sustainable strategy to prepare ultra-lightweight microwave absorbers with excellent EM wave absorbing ability utilizing biomass precursor and MOF. Graphical abstract: A hierarchical carbon fiber coated with dodecahedral Co/C nanoparticles and villus-like CNTs was fabricated using cotton and ZIF-67(HCF@CZ-CNTs), which shows ultra-low apparent density (0.0198 g/cm 3 ), minimum −53.5 dB microwave reflection loss at 7.8 GHz as well as broad effective absorption bandwidth of 8.02 GHz. Image 1